Extraskeletal Myxoid Chondrosarcomas: Combined Modality Therapy With Both Radiation and Surgery Improves Local Control. (October 2019) - Bishop, Andrew J.; Bird, Justin E.; Conley, Anthony P.; Roland, Christina L.; Moon, Bryan S.; Satcher, Robert L.; Livingston, John A.; Patel, Shreyaskumar; Wang, Wei-Lien; Lazar, Alexander J.; Lewis, Valerae O.; Lin, Patrick P.; et al.
Abstract : Objective: We evaluated our experience treating patients with localized extraskeletal myxoid chondrosarcomas (EMCs) to evaluate outcomes and relapse rates in order to better inform treatment decisions for these rare soft tissue sarcomas. Materials and Methods: We reviewed the records of 41 consecutive patients with localized EMC treated at our institution from 1990 to 2016. Most patients (n=33, 80%) received combined modality therapy with surgery and radiation therapy, whereas only 8 (20%) underwent surgery alone. The Kaplan-Meier method was used to estimate rates of overall survival, disease-specific survival, local control (LC), and distant metastatic-free survival (DMFS). Results: Median follow-up time was 94 months (range, 8 to 316). The 10-year LC, DMFS, disease-specific survival, and overall survival rates were 90%, 69%, 85%, and 66%, respectively. There were 5 patients (12%) with local relapse at a median time of 75 months (range, 13 to 176). On univariate analysis, the only significant factor associated with poorer LC was the use of surgery alone (10 y LC, 63% vs. 100% for combined modality therapy, P =0.004), which remained the only factor also significant on the multivariable analysis ( P =0.02; hazard ratio [HR], 12.7; 95% confidence interval [CI], 1.4-115.3). In total, 13 patients (32%) developed distant metastatic at a median time of 28 months (range, 3 to 154). Interestingly, local recurrence was the only factor associated with poorer DMFS on multivariate analysis ( P =0.04; HR, 3.9; 95% CI, 1.1-14.7). Conclusions: For patients with EMC, surgery alone was associated with a higher risk of local recurrence. Therefore, we recommend optimal local therapeutic strategies upfront with both surgery and radiation therapy to reduce the risk of local and ultimately distant recurrence.